Effectiveness of A-Ba-Te Innovation (Let's Eradicate Tuberculosis) on Self-Care Management among TB Patients in Public Health Center - Hidayat, Taofik; Janah, Esti Nur; Rohmiati, Marti Dwi; Umami, Fasikhatul (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: This study examines the effectiveness of the A-Ba-Te innovation in promoting self-care among TB patients in the Sirampog Health Center service area. Methods: A quasi-experimental design with one group was observed on the dependent variable after intervention (one group pretest-posttest design). The study involved 22 respondents who received treatment at the Sirampog Health Center over four weeks. They were given the "ABATE innovation," which included health education on TB disease, TB medication, self-care training, deep breathing exercises, effective coughing techniques, relaxation techniques, and semi-Fowler position management. Results: Hypothesis testing used an independent T-Test with a significance level of 0.000, indicating a significant change in respondents before and after the treatment. The change was observed from a mean difference value of -35.818, indicating an increase of 35.818. Conclusion: This study concluded that the A-Ba-Te innovation is effective in improving Self-Care Management for TB Patients in the Sirampog Health Center service area. Conclusions : The A-Ba-Te innovation, which includes health education, deep breathing exercises, effective coughing, semi-Fowler's position, and daily medication reminders via WhatsApp, has significantly improved self-care management in tuberculosis patients.